Associations of Late-Life Sleep Medication Use With Incident Dementia in the Atherosclerosis Risk in Communities Study. Issue 3 (14th April 2022) - Full, Kelsie M; Pusalavidyasagar, Snigdha; Palta, Priya; Sullivan, Kevin J; Shin, Jung-Im; Gottesman, Rebecca F; Spira, Adam P; Pase, Matthew P; Lutsey, Pamela L
Abstract: Background: Sleep medications may contribute to dementia development or indicate sleep disturbances that are markers of or contributors to neurologic disease. The objective of this study was to examine the use of sleep medications and incident dementia in a community-based cohort of older adults. We hypothesize late-life sleep medication use is associated with a greater risk of dementia. Methods: The Atherosclerosis Risk in Communities (ARIC) study is an ongoing community-based cohort study. ARIC participants taking barbiturates, benzodiazepines, antidepressants, non-benzodiazepine receptor agonists (Z-drugs), or other hypnotics in 2011–2013 were categorized as sleep medication users. Participants were followed through 2019 for incident dementia. Logistic regression propensity scores were used to match sleep medication users with nonusers (1:2). Cox proportional hazards regression models were used to estimate hazard ratios (HR) for time to dementia diagnosis with adjustment for demographics, lifestyle characteristics, and cardiovascular risk factors. Results: One-quarter of the eligible ARIC participants used sleep medications. In the matched sample ( N = 4 197; 69% female; mean age 75.3 + 5.0 years), 632 dementia cases were ascertained over a median follow-up of 6.5 years. In the fully adjusted model, sleep medication use compared to nonuse was associated with a 48% greater risk of dementia (HR: 1.48; 95% confidence interval (CI): 1.26–1.74). Conclusion: To expand on these findings, studies with longer follow-up and earlier assessment of sleep medication use are needed. Furthermore investigation of the potential dose-response association of multiple sleep medications and the potential causal role of sleep medications in the development of dementia may be clinically meaningful.